2012
DOI: 10.1016/j.jtcvs.2011.09.033
|View full text |Cite
|
Sign up to set email alerts
|

A heart team’s perspective on interventional mitral valve repair: Percutaneous clip implantation as an important adjunct to a surgical mitral valve program for treatment of high-risk patients

Abstract: Clip-based percutaneous mitral valve repair is a safe, low-risk, and effective therapeutic option in symptomatic patients with a high risk for surgery and does not exclude later surgical repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 16 publications
0
36
0
Order By: Relevance
“…As in previous studies, clip embolization was not observed in the present registry. In fact, only a single case of clip embolization has been reported worldwide, so far [1,[3][4][5]8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table V). Partial clip detachment from one leaflet was rarely observed (2% in the present analysis) and occurred spontaneously or during advancement of a second clip for residual MR.…”
Section: Discussionmentioning
confidence: 99%
“…As in previous studies, clip embolization was not observed in the present registry. In fact, only a single case of clip embolization has been reported worldwide, so far [1,[3][4][5]8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] (Table V). Partial clip detachment from one leaflet was rarely observed (2% in the present analysis) and occurred spontaneously or during advancement of a second clip for residual MR.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19][20][21][22][23][24][25][26][27] A recent pooled analysis of 351 patients in the EVEREST II High Risk Registry and the REALISM (Real World Expanded Multi-center Study of the MitraClip System) Continued Access Study demonstrated an implantation success of 96%. 19 These patients were all considered high risk for surgery (estimated Society of Thoracic Surgeons score >12%).…”
Section: Evidence From Registriesmentioning
confidence: 99%
“…In the early postoperative course, the MAE Multimorbidity, high-risk patient, contraindication for oMVS: log EuroScore > 20% and/or STS-Score >10% 11,13,14,19,21,24,26,31,35,42,43,48,49 AHA/ASC/ESC criteria for oMVS fulfilled [10][11][12]20,21,38,40,43,45,47,50 Previous cardiac surgery 13,14,20,26,40,45 Echocardiographic criteria for treatment with MitraClip system fulfilled 8,9,19,32,33 Chest radiation/porcelain aorta 8,9,16,26,45,51 Possible indications…”
Section: Recommendations For Structural Procedural and Documentatiomentioning
confidence: 99%